O44: WOUND HEALING INFLAMMATORY MARKERS PREDICT PROGNOSIS AND SURVIVAL IN EARLY BREAST CANCER. (27th April 2021) - Singh, U; Castle, J; Greenhalgh, S; Hussain, U; Descamps, T; Nash, S; Wilson, M; Hunt, R; Kirwan, CC
Abstract: Introduction: Cancer is likened to a non-healing wound. There is limited evidence on the expression of wound healing tissue inflammatory markers, CD68(pan-macrophage marker), HO-1(tumour cell marker) and FAP(cancer-associated fibroblast marker) in human breast cancer. Method: In 201 invasive breast cancer and 58 DCIS patients, CD68+TAM expression, tumour HO-1 and fibroblast FAP expression, quantified by immunohistochemistry(dichotomised: high/present vs low/absent), was correlated with tumour factors (grade, proliferation(Ki67), ER, HER2); demographic factors, behavioural factors (smoking, alcohol) and survival status(DFS, OS) Result: High CD68+macrophage expression was increased in invasive breast cancer, compared to DCIS, and normal tissue distant from the tumour(59%, 41%and 6% respectively; p<0.001).In invasive cancer, CD68+TAM expression increased with increasing tumour grade(Grade 1:42%, Grade 2:58%, Grade 3:72%; p=0.006), high Ki67(71%vs.47%; p=0.004), ER negativity(79.4%vs.55.4%; p=0.01) and HER2(HER2 positive 81.8% vs. HER2 negative 56.3%; p=0.03). CD68+TAM expression was higher in high compared to low/intermediate grade DCIS(44% % vs. 31% p=0.52). CD68+TAM expression was increased in patients who self-reported alcohol intake(non-drinker 43% vs. drinker 62%; p=0.01). HO-1 was associated with shorter DFS(HR:3.22, p=0.027) and OS(HR:2.86, p=0.029).FAP fibroblast expression correlated with longer DFS (HR:0.296, p=0.029) and OS (HR:0.271, p=0.008). Conclusion: Tumour inflammation as assessed by CD68+TAM expression shows utility in identifying aggressive breast cancer sub-types. The association reported between CD68+TAM density and alcohol intake suggests a possible mechanism for alcohol as a risk factor for breast cancer. The prognostic value of HO-1 and FAP expression demonstrated here suggests a functional role of these wound healing markers in breast cancer. HO-1:Heme-oxygenase-1; FAP:Fibroblast activation protein; TAM:Tumour associated macrophage; DCIS: Ductal carcinoma in situ Take-home message: Wound healing pathways of inflammation may be implicated in early breast cancer development